Caracterização e análise macro e microestrutural de concretos fabricados com cimentos contendo escórias de alto-forno - Aldo Giuntini de Magalhaes (2007)
The worldwide concern with the sustainable development has placed restrictions on the use of raw materials and on gas emissions in the atmosphere. In this scenario, the Brazilian cement industry has made significant changes in Portland cement compositions. These changes include the increasing proportions of mineral additions such as blast-furnace slag. These alterations in the cements promote significant changes in the kinetics of the hydration process and in the microstructure of the concrete which in turn generate changes on the behavior and durability of the reinforced concrete structures. The goal of the thesis is the characterization and analyses of the microstructure of the concretes cast with blast-furnace slag Portland cements with the durability and the mechanical properties of the material. Concretes with axial compressive strength of 30 and 40 MPa produced with the Brazilian type CP II E 32 and CP III 32 were cast and investigated. The microstructure analysis, made at different times during the cement hydration process period, includes X-rays diffraction, thermal analyses, scanning electron microscopy, mercury and helium picnometry, mercury porosimetry and nitrogen adsorption. The axial compressive strength, the secant modulus of elasticity, and water permeability, accomplished in coincident dates with the microstructure analyses, were the properties employed to appraise the mechanical behavior and durability of the concrete. The test results described herein evaluated quantitatively the macrostructure behavior and qualitatively the microstructure properties pointing out the potentialities and limitations of the used techniques. These macro and microstructure concrete results may contribute to aid future research concerning with the material behavior with respect to time. A better understanding of concrete microstructure will certainly promote economical gains and the performance of the material.